THE EFFECTIVENESS OF IMPLEMENTING THE GUIDED READING METHOD IN IMPROVING THE READING LITERACY OF STUDENTS OF SMPN 40 MAKASSAR - Baa, Sultan; La Sunra, La Sunra (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research aims to investigate the effectiveness of implementing the Guided Reading method in increasing the reading literacy of students at SMPN 40 Makassar. The research method used was a quasi-experiment with a single group control pre-test and post-test design. The research sample consisted of two classes, where one class was used as an experimental group that received the Guided Reading method treatment, while the other class acted as a control group that received conventional learning. Data was collected through reading literacy tests before and after treatment, as well as through observation of the learning process. The results of the data analysis show a significant increase in the reading literacy scores of students who took part in learning using the Guided Reading method compared to the control group. In addition, observations revealed a higher level of involvement and interest from students in learning using the Guided Reading method. These findings confirm that the effective application of the Guided Reading method can improve the reading ability of SMPN 40 Makassar students and stimulate their interest in the learning process. The practical implication of this research is the importance of considering the use of appropriate learning methods in increasing reading literacy at the secondary school level. It is hoped that the results of this research can contribute to the development of more effective learning strategies to improve students’ reading skills in secondary schools.